2017
DOI: 10.1111/maec.12440
|View full text |Cite
|
Sign up to set email alerts
|

Tourism impacts on benthic communities of sandy beaches

Abstract: This study evaluated the effect of human trampling on the benthic macrofauna of two beaches in Southeast Brazil with different levels of intensity of tourism, Grussaí (more impacted) and Manguinhos (less impacted), during periods of high and low tourism activity. The macrofauna of urbanized (U) and non‐urbanized (NU) sectors of the inter‐tidal zone was sampled and the number of visitors was recorded. General linear models revealed a decreasing in abundance of macrofauna species in the urbanized sectors of anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 39 publications
(69 reference statements)
0
24
0
2
Order By: Relevance
“…Mean density was 122.6 organisms during the week and only 21.8 during the weekend in the Urca Beach (Table 3). As showed by Machado et al (2017), the consequences of human impacts should generate chronic responses, reducing the density of certain species through seasons, as happened with H. californiensis and nemerteans during winter on their study. In the present study, we observed an opposite result in the Fora Beach with significant statistical differences, both during the summer and winter.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Mean density was 122.6 organisms during the week and only 21.8 during the weekend in the Urca Beach (Table 3). As showed by Machado et al (2017), the consequences of human impacts should generate chronic responses, reducing the density of certain species through seasons, as happened with H. californiensis and nemerteans during winter on their study. In the present study, we observed an opposite result in the Fora Beach with significant statistical differences, both during the summer and winter.…”
Section: Discussionmentioning
confidence: 96%
“…In that study it was possible to verify a drastic change in abundance of some crustacean species, such as Atlantorchestoidea brasiliensis (Dana 1853), which was completely absent in the highly urbanized beach sampled (Cardoso et al 2016). Machado et al (2017) performed a very similar study about human trampling comparing two beaches in the Rio de Janeiro state, one highly urbanized and another non-urbanized. They verified that there is an impact only in the highly urbanized sectors, mainly in soft body organisms such as Nemertea and the polychaete H. californiensis, an abundant species in that region (Machado et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we used wave height and wave period as metrics for storm intensity (Newton et al , ). In the study region, waves higher than 2 m are indicative of stormy conditions (Machado et al , ). Our analysis does not include frequency and duration of storms, because in the region studied, several peaks of wave height are observed over the months, preventing a precise distinction between stormy wave episodes (Machado et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Entre estas actividades destacan la compresión de suelos, supresión de las dunas y reducción del aporte sedimentario (cf. Machado et al, 2017), sobrepesca y pesca destructiva (Javaid et al, 2017), contaminación por efluentes urbanos y agrícolas (Liñán-Cabello et al, 2016), operaciones de dragado (Rehitha et al, 2017), transferencia de residuos sólidos desde tierra (Williams et al, 2016) y derrames petroleros (Buskey et al, 2016), entre otros.…”
Section: Introductionunclassified